2018
DOI: 10.1186/s12906-018-2223-8
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin derivative, 2,6-bis(2-fluorobenzylidene)cyclohexanone (MS65) inhibits interleukin-6 production through suppression of NF-κB and MAPK pathways in histamine-induced human keratinocytes cell (HaCaT)

Abstract: BackgroundHistamine is a well-known mediator involved in skin allergic responses through up-regulation of pro-inflammatory cytokines. Antihistamines remain the mainstay of allergy treatment, but they were found limited in efficacy and associated with several common side effects. Therefore, alternative therapeutic preferences are derived from natural products in an effort to provide safe yet reliable anti-inflammatory agents. Curcumin and their derivatives are among compounds of interest in natural product rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…We next questioned how histamine activated the COX-2 signaling pathway in hUCB-MSCs. Histamine is known to induce the mobilization of intracellular calcium and the activation of MAPKs 45, 46, which play a pivotal role in the stimulation of NF-κB and the subsequent COX-2 signal 47, 48. In the present study, we showed that histamine could alter intracellular Ca 2+ mobilization and lead to the phosphorylation of MAPK and NF-κB, as described in previous reports 45, 46, 49, 50.…”
Section: Discussionsupporting
confidence: 88%
“…We next questioned how histamine activated the COX-2 signaling pathway in hUCB-MSCs. Histamine is known to induce the mobilization of intracellular calcium and the activation of MAPKs 45, 46, which play a pivotal role in the stimulation of NF-κB and the subsequent COX-2 signal 47, 48. In the present study, we showed that histamine could alter intracellular Ca 2+ mobilization and lead to the phosphorylation of MAPK and NF-κB, as described in previous reports 45, 46, 49, 50.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, Compared to Sham operated Group, NF-κB p65 is up-regulated in Model Group. NF-κB p65 is a classic inflammation marker, for instance, IKK/IκB/NF-κB p65 inflammatory cascades involves in many inflammatory physiological actions [17]. The suppression of IKK/IκB/NF-κB p65 inflammatory cascades can prevent their translocation into nucleus so as to inhibit IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…Another research has indicated that curcumin regulates the activation of certain transcription factors such as activating protein‐1 and NF‐κB in stimulated monocytes and alveolar macrophages, thus blocking cytokine gene expression (Farhangkhoee, Khan, Chen, & Chakrabarti, ). It is reported that curcumin can down‐regulate the induced activation of NF‐κB from various inflammatory stimuli and inhibit IκB kinase activation, which is needed for NF‐κB further activation (Razali, Nazarudin, Lai, Abas, & Ahmad, ; Figure ). Moreover, curcumin modulates the inflammatory response by down‐regulating the activity of cyclooxygenase‐2, lipoxygenase, and inducible nitric oxide synthase enzymes.…”
Section: Several Main Antioxidative and Anti‐inflammatory Cellular Simentioning
confidence: 99%